Fischereisituation, Probennahme und Zustand der Nutzfischbestände im Nordostatlantik im Jahre 2002 - Schöne, Rüdiger (2003)
NE-arctic cod, saithe, haddock, redfish and Greenland halibut are important fish stocks of the European fisheries. In many European countries national data sampling projects on commercial fisheries have been established in recent years. Since 1990 German investigations in the NE-Atlantic have been mainly carried out on the commercial trawler FMS KIEL. The results of these sea samplings are used as German basic data for stock assessments of the “Arctic Fisheries Working Group” of the International Council for the Exploration of the Seas (ICES). Biological investigations were carried out in Norwegian waters, the Svalbard area and the Barents Sea (ICES Divisions I, IIa and IIb) on board FMS KIEL in March and October/November 2002. This report presents results of these cruises and an overview over the general fishery situation in 2002. Finally, results and recommendations on the scientific stock assessments of cod, saithe, haddock, redfishand Greenland halibut are reported.